À la Recherche de Yankee Art - Dimitrios S. Latsis (Transatlantica)
In 1938 the Museum of Modern Art organized a US government-funded, multi-disciplinary exhibition in Paris, entitled “Three Centuries of American Art.” In this paper I explore the geopolitical, aesthetic and cultural dimensions of the exhibition as an episode of cultural diplomacy in Franco-American relations and as an attempt to promote, for the first time, an American ‘national artistic scene’ to the world. Special focus is placed on the selection of artworks and on curatorial practice. A comparison is offered with the sole precedent: an exhibition of American Art staged immediately after the end of WW I. A complex intertextual and intermedial web emerges from this comparison that reveals various tensions around an emerging “narrative” for the self-representation of the United States as a world-power and an artistically “emancipated” nation and provides a glimpse into a New Deal-era attempt at cultural diplomacy on the eve of WW II. These poles ultimately converge to indicate the role that “region” and “place” assumed in the American imaginary of the nineteenth century as it reverberated in interesting political and aesthetic ways in the first decades of the twentieth.